The Influence of Indirect Compensation and Intrinsic Motivation on Employee Productivity (Case Study: PT. Primarindo Asia Infrastructure Tbk Bandung) - Ermi Triaji; Nabilah Maharani Putri (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This study examines the effects of indirect compensation and intrinsic motivation on employee productivity at PT. Primarindo Asia Infrastructure Tbk Bandung. The research addresses key challenges in managing productivity, emphasizing the significance of non-monetary benefits and intrinsic drivers in enhancing employee performance. These factors are critical in today’s competitive work environment, particularly in manufacturing sectors, where maintaining consistent productivity levels is paramount. The study aims to provide actionable insights into human resource management practices that align compensation and motivation strategies to improve employee productivity. A quantitative descriptive verificative approach was employed, with data collected from 77 respondents using a structured questionnaire and analyzed through path analysis. The questionnaire items underwent validity and reliability testing to ensure accuracy. Correlation and path analyses were conducted to evaluate direct and indirect effects of the independent variables on employee productivity. Findings indicate that indirect compensation contributes to employee productivity through both direct and indirect pathways, with a total effect of 35.81%. Intrinsic motivation emerged as the stronger determinant, accounting for a total effect of 44.46% on productivity. Together, these variables explain 72.8% of the variance in employee productivity, highlighting their complementary roles. Employees perceive indirect compensation as satisfactory, valuing social security, benefits, and work-life balance. High intrinsic motivation levels further reflect employees’ satisfaction with personal achievements, recognition, and opportunities for growth. The study recommends enhancing social security programs, fostering employee autonomy, and supporting motivation under challenging conditions to optimize productivity. These findings underscore the importance of strategic HR practices in fostering a productive and engaged workforce.